2020
DOI: 10.1093/abbs/gmaa113
|View full text |Cite
|
Sign up to set email alerts
|

22q11.2 deletion syndrome and schizophrenia

Abstract: 22q11.2 deletion is a common microdeletion that causes an array of developmental defects including 22q11.2 deletion syndrome (22q11DS) or DiGeorge syndrome and velocardiofacial syndrome. About 30% of patients with 22q11.2 deletion develop schizophrenia. Mice with deletion of the ortholog region in mouse chromosome 16qA13 exhibit schizophrenia-like abnormal behaviors. It is suggested that the genes deleted in 22q11DS are involved in the pathogenesis of schizophrenia. Among these genes, COMT, ZDHHC8, DGCR8, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 118 publications
0
16
0
Order By: Relevance
“…Although our main limitation is that neuronal antibodies were negative in our patient’s serum and CSF, which are mandatory to reach a definite diagnosis ( 9 ), she presented other characteristic clinical features that strongly suggest an NMDAR-like AE, such as paradoxical worsening of psychotic symptoms and dyskinetic movements after antipsychotic administration ( 12 ). Nevertheless, the psychotic symptoms could be explained by the inclusion of schizophrenia susceptibility genes as DGCR8, DGCR2, ZDHHC8, and PRODH within the microdeletion responsible for 22q11DS ( 13 ). Similarly, antipsychotic intolerance could be explained by the inclusion of the gene COMT, which encodes an enzyme involved in the dopaminergic metabolism ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although our main limitation is that neuronal antibodies were negative in our patient’s serum and CSF, which are mandatory to reach a definite diagnosis ( 9 ), she presented other characteristic clinical features that strongly suggest an NMDAR-like AE, such as paradoxical worsening of psychotic symptoms and dyskinetic movements after antipsychotic administration ( 12 ). Nevertheless, the psychotic symptoms could be explained by the inclusion of schizophrenia susceptibility genes as DGCR8, DGCR2, ZDHHC8, and PRODH within the microdeletion responsible for 22q11DS ( 13 ). Similarly, antipsychotic intolerance could be explained by the inclusion of the gene COMT, which encodes an enzyme involved in the dopaminergic metabolism ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, 22q11.2 deletion is associated with several psychiatric diseases, such as psychosis, mood and anxiety disorders, and attention deficit hyperactivity disorder (ADHD) [ 160 ]. Studies have shown that subjects with 22q11.2 deletion exhibit a 25% risk of developing schizophrenia symptoms, whereas the prevalence in the general population is up to 1% [ 161 ].…”
Section: Genetic Modelsmentioning
confidence: 99%
“…1 Also known as "DiGeorge syndrome", microdeletion in this region contributes to defective development of the pharyngeal pouch system in early embryonic life and, as such, there are a wide range of clinical phenotypes associated with 22q11.2 deletion syndrome. [1][2][3][4] Structural abnormalities commonly associated with this condition include conotruncal cardiac defects, thymic hypoplasia, craniofacial abnormalities (including cleft palate), gastrointestinal and genitourinary malformations, poor growth, and even problems with thyroid and parathyroid development. [1][2][3] Postnatally, those with 22q11.2 deletion syndrome can also present with hypocalcemia, immunodeficiency, and failure to thrive.…”
Section: Introductionmentioning
confidence: 99%